eDNA metabarcoding survey reveals fine‐scale coral reef community variation across a remote, tropical island ecosystem - Katrina M. West; Michael Stat; Euan S. Harvey; Craig L. Skepper; Joseph D. DiBattista; Zoe T. Richards; Michael J. Travers; Stephen J. Newman; Michael Bunce (Molecular Ecology, 2020)
Environmental DNA (eDNA) metabarcoding, a technique for retrieving multispecies DNA from environmental samples, can detect a diverse array of marine species from filtered seawater samples. There is a growing potential to integrate eDNA alongside existing monitoring methods in order to establish or improve the assessment of species diversity. Remote island reefs are increasingly vulnerable to climate‐related threats and as such there is a pressing need for cost‐effective whole‐ecosystem surveying to baseline biodiversity, study assemblage changes and ultimately develop sustainable management plans. We investigated the utility of eDNA metabarcoding as a high‐resolution, multitrophic biomonitoring tool at the Cocos (Keeling) Islands, Australia (CKI)—a remote tropical coral reef atoll situated within the eastern Indian Ocean. Metabarcoding assays targeting the mitochondrial 16S rRNA and CO1 genes, as well as the 18S rRNA nuclear gene, were applied to 252 surface seawater samples collected from 42 sites within a 140 km 2 area. Our assays successfully detected a wide range of bony fish and elasmobranchs (244 taxa), crustaceans (88), molluscs (37) and echinoderms (7). Assemblage composition varied significantly between sites, reflecting habitat partitioning across the island ecosystem and demonstrating the localisation of eDNA signals, despite extensive tidal and oceanic movements. In addition, we document putative new occurrence records for 46 taxa and compare the efficiency of our eDNA approach to visual survey techniques at CKI. Our study demonstrates the utility of a multimarker metabarcoding approach in capturing multitrophic biodiversity across an entire coral reef atoll and sets an important baseline for ongoing monitoring and management.

Geographic structure and host specificity shape the community composition of symbiotic dinoflagellates in corals from the Northwestern Hawaiian Islands - Michael Stat; Denise M. Yost; Ruth D. Gates (Coral Reefs, 2015)

Exploring Symbiodinium diversity and host specificity in Acropora corals from geographical extremes of W estern A ustralia with 454 amplicon pyrosequencing - L. Thomas; G. A. Kendrick; W. J. Kennington; Z. T. Richards; M. Stat (Molecular Ecology, 2014)
Scleractinian corals have demonstrated the ability to shuffle their endosymbiotic dinoflagellate communities (genus Symbiodinium) during periods of acute environmental stress. This has been proposed as a mechanism of acclimation, which would be increased by a diverse and flexible association with Symbiodinium . Conventional molecular techniques used to evaluate Symbiodinium diversity are unable to identify genetic lineages present at background levels below 10%. Next generation sequencing ( NGS ) offers a solution to this problem and can resolve microorganism diversity at much finer scales. Here we apply NGS to evaluate Symbiodinium diversity and host specificity in Acropora corals from contrasting regions of Western Australia. The application of 454 pyrosequencing allowed for detection of Symbiodinium operational taxonomic units ( OTU s) occurring at frequencies as low as 0.001%, offering a 10 000‐fold increase in sensitivity compared to traditional methods. All coral species from both regions were overwhelmingly dominated by a single clade C OTU (accounting for 98% of all recovered sequences). Only 8.5% of colonies associated with multiple clades (clades C and D , or C and G ), suggesting a high level of symbiont specificity in Acropora assemblages in Western Australia. While only 40% of the OTU s were shared between regions, the dominance of a single OTU resulted in no significant difference in Symbiodinium community structure, demonstrating that the coral‐algal symbiosis can remain stable across more than 15° of latitude and a range of sea surface temperature profiles. This study validates the use of NGS platforms as tools for providing fine‐scale estimates of Symbiodinium diversity and can offer critical insight into the flexibility of the coral‐algal symbiosis.

Symbiotic specificity, association patterns, and function determine community responses to global changes: defining critical research areas for coral‐ Symbiodinium symbioses - Nicholas S. Fabina; Hollie M. Putnam; Erik C. Franklin; Michael Stat; Ruth D. Gates (Global Change Biology, 2013)
Climate change‐driven stressors threaten the persistence of coral reefs worldwide. Symbiotic relationships between scleractinian corals and photosynthetic endosymbionts (genus Symbiodinium ) are the foundation of reef ecosystems, and these associations are differentially impacted by stress. Here, we couple empirical data from the coral reefs of Moorea, French Polynesia, and a network theoretic modeling approach to evaluate how patterns in coral‐ Symbiodinium associations influence community stability under climate change. To introduce the effect of climate perturbations, we simulate local ‘extinctions’ that represent either the loss of coral species or the ability to engage in symbiotic interactions. Community stability is measured by determining the duration and number of species that persist through the simulated extinctions. Our results suggest that four factors greatly increase coral‐ Symbiodinium community stability in response to global changes: (i) the survival of generalist hosts and symbionts maximizes potential symbiotic unions; (ii) elevated symbiont diversity provides redundant or complementary symbiotic functions; (iii) compatible symbiotic assemblages create the potential for local recolonization; and (iv) the persistence of certain traits associate with symbiotic diversity and redundancy. Symbiodinium may facilitate coral persistence through novel environmental regimes, but this capacity is mediated by symbiotic specificity, association patterns, and the functional performance of the symbionts. Our model‐based approach identifies general trends and testable hypotheses in coral‐ Symbiodinium community responses. Future studies should consider similar methods when community size and/or environmental complexity preclude experimental approaches.

The endosymbiotic dinoflagellates (Symbiodinium sp.) of corals are parasites and mutualists - M. P. Lesser; M. Stat; R. D. Gates (Coral Reefs, 2013)

Stability of coral–endosymbiont associations during and after a thermal stress event in the southern Great Barrier Reef - M. Stat; W. K. W. Loh; T. C. LaJeunesse; O. Hoegh-Guldberg; D. A. Carter (Coral Reefs, 2009)

Symbiont acquisition strategy drives host–symbiont associations in the southern Great Barrier Reef - M. Stat; W. K. W. Loh; O. Hoegh-Guldberg; D. A. Carter (Coral Reefs, 2008)